2013
DOI: 10.2319/050313-338.1
|View full text |Cite
|
Sign up to set email alerts
|

A better statistical method of predicting postsurgery soft tissue response in Class II patients

Abstract: The multivariate PLS method was more satisfactory than the OLS method in accurately predicting the soft tissue profile change after surgical correction of severe Class II malocclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…By the same token, because of repositioning and rotation of the mandible, the new most anterior soft-tissue point of the chin (soft-tissue pogonion) may not reflect the presurgical soft-tissue pogonion. 13,23 As in most commercial software, a Bezier spline function is used to connect the landmark points, creating a gentle smooth curve. 6 By using the Bezier spline function, a prediction error (Figs 2 and 3) that is located along the Bezier curve (Fig 4) becomes more tolerable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By the same token, because of repositioning and rotation of the mandible, the new most anterior soft-tissue point of the chin (soft-tissue pogonion) may not reflect the presurgical soft-tissue pogonion. 13,23 As in most commercial software, a Bezier spline function is used to connect the landmark points, creating a gentle smooth curve. 6 By using the Bezier spline function, a prediction error (Figs 2 and 3) that is located along the Bezier curve (Fig 4) becomes more tolerable.…”
Section: Resultsmentioning
confidence: 99%
“…26 In addition, the improved accuracy of the PLS method is most likely because the soft-tissue response at a specific point highly depends on its adjacent soft-tissue response: ie, the interdependency of soft-tissue points. 13 However, the aforementioned investigation had only been performed for mandibular setback surgeries alone. Class III 2-jaw surgery patients had not yet been included.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al 1 previously suggested a multivariate prediction method for Class II surgery patients. In the study by Lee et al, 1 80 patients provided the training data set that was used to build the prediction algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…1 This method was based on a multivariate partial least squares regression (PLS) that returned more accurate prediction results than conventional methods. For the validity of this new prediction method to be confirmed, its prediction errors should also be reliable for other types of patients and additional data sets.…”
Section: Introductionmentioning
confidence: 99%